Optimizing Thermal Comfort in Urban Squares of Hot-Humid Regions: A Case Study Considering Tree Growth, Species, and Planting Intervals - Yixuan Xiao; Yong Huang; Xinchen Pan (Atmosphere)
The worsening urban thermal environment has become a critical challenge in many cities. Trees, as vital components of urban green spaces, provide multiple ecosystem services, especially in improving the microclimate. However, limited studies address how morphological changes during tree growth influence their cooling benefits. This study combined the tree growth model with ENVI-met to simulate 27 scenarios in a subtropical urban square, considering three planting intervals, three urban tree species, and three growth stages to evaluate their daytime thermal impacts. The key findings include: (1) Tree size and planting intervals are more important than tree quantity in enhancing thermal comfort. (2) Reducing intervals by 2 m enhances cooling effects but minimally affects PET (physiological equivalent temperature). (3) Increasing DBH (diameter at breast height) significantly improves cooling. For every 10 cm increase in DBH, Michelia alba, Mangifera indica, and Ficus microcarpa L. f. reduced solar radiation by 19.54, 18.09, and 34.50 W/m2, and mean radiant temperature by 0.61 °C, 0.68 °C, and 1.35 °C, respectively, while decreasing PET by 0.23 °C, 0.23 °C, and 0.46 °C. These findings provide empirical evidence and practical recommendations for designing comfortable open spaces in subtropical cities.